2016
DOI: 10.1002/anie.201604021
|View full text |Cite
|
Sign up to set email alerts
|

CuxCo1−xO Nanoparticles on Graphene Oxide as A Synergistic Catalyst for High‐Efficiency Hydrolysis of Ammonia–Borane

Abstract: Ammonia-borane (AB) is an excellent material for chemical storage of hydrogen. However, the practical utilization of AB for production of hydrogen is hindered by the need of expensive noble metal-based catalysts. Here, we report Cux Co1-x O nanoparticles (NPs) facilely deposited on graphene oxide (GO) as a low-cost and high-performance catalyst for the hydrolysis of AB. This hybrid catalyst exhibits an initial total turnover frequency (TOF) value of 70.0 (H2 ) mol/(Cat-metal) mol⋅min, which is the highest TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
124
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(136 citation statements)
references
References 28 publications
(87 reference statements)
6
124
1
Order By: Relevance
“…Cu has emerged as an interesting transition metal with its catalytic power toward AB hydrolysis or methanolysis [18][19][20][21]. In the past, the activity of Cu for dehydrogenation of AB can be significantly improved by compositing with other elemental atoms or supporting on substrate [22][23][24][25][26][27][28][29][30]. Although the multi-component systems have shown remarkable catalytic efficiencies, their tedious and costly fabrication process hinders their widespread application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu has emerged as an interesting transition metal with its catalytic power toward AB hydrolysis or methanolysis [18][19][20][21]. In the past, the activity of Cu for dehydrogenation of AB can be significantly improved by compositing with other elemental atoms or supporting on substrate [22][23][24][25][26][27][28][29][30]. Although the multi-component systems have shown remarkable catalytic efficiencies, their tedious and costly fabrication process hinders their widespread application.…”
Section: Introductionmentioning
confidence: 99%
“…Since Fe(OH) 3 can be produced on a large scale and is insoluble in water or methanol, it might be wise to employ it as a support for Cu to form a composite material toward the dehydrogenation of AB. This composite will give several benefits: first, just like in the case of metal-organic frameworks [4,12,29] and carbon materials [5,9,28], Fe(OH) 3 can be utilized for restraining the agglomeration or sintering of the in-situ formed Cu(0); second, an interfacial interaction can be expected between Cu(0) and Fe species to facilitate the reaction; finally, the OH À in Fe(OH) 3 may accelerate the reaction through the activation of B-N bonds. Thus, a multipronged synergistic effect can be expected between Cu(0) and Fe(OH) 3 to facilitate the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of porous materials that could support ultrafine noble metal nanoparticles (NMNPs), prevent NMNPs from aggregation and leaching is a very meaningful and challenging work . Various inorganic supporting materials such as mesoporous silica, activated carbon, graphene materials, mesoporous carbon have been developed and used for fabricating supported catalyst with well‐dispersed NMNPs. However, due to the weak Van der Waals forces between the supporting materials and NMNPs, the NMNPs easily aggregate into larger NPs and leach into the solution, leading to the deactivation of the catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Yasukawa et al prepared N‐doped carbon‐supported Co/Cu bimetallic NPs catalysts for aerobic oxidative of esterifications . Feng et al reported Cu x Co 1‐x O NPs anchored on graphene oxide as a synergistic catalyst for efficient hydrolysis of ammonia borane . However, these catalysts are usually prepared by deposition‐reduction technique, thus easily suffer from poor stability and weak interaction between metals.…”
Section: Methodsmentioning
confidence: 99%